Our ancient national airs : Scottish song collecting from the enlightenment to the romantic era - McAulay, Karen (Karen Elisabeth) (Music in nineteenth-century Britain., 2013)
Karen McAulay traces the complex history of Scottish song collecting, and the publication of major Highland and Lowland collections. Looking at sources, authenticity, collecting methodology and format, McAulay places these collections in their cultural context. Attention is given to some of the performance issues raised, either in correspondence or in the paratexts of published collections; and the narrative is interlaced with references to contemporary literary, social and even political history as it affected the collectors themselves. Most significantly, this study demonstrates a resurgence.